The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/vaccines9030221
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Reactions to Current Available COVID-19 Vaccinations: Pathophysiology, Causality, and Therapeutic Considerations

Abstract: Vaccines constitute the most effective medications in public health as they control and prevent the spread of infectious diseases and reduce mortality. Similar to other medications, allergic reactions can occur during vaccination.While most reactions are neither frequent nor serious, anaphylactic reactions are potentially life-threatening allergic reactionsthat are encountered rarely, but can cause serious complications.The allergic responses caused by vaccines can stem fromactivation of mast cells via Fcε rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
216
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(225 citation statements)
references
References 65 publications
(43 reference statements)
3
216
1
5
Order By: Relevance
“…A DVT has also been reported shortly after the second dose of an mRNA-based vaccine as well [ 52 ]. Anaphylaxis as an acute allergic reaction has also been reported as a rare event for some vaccines, such as mRNA COVID-19 vaccines [ 53 ] and adenovector vaccines against COVID-19 [ 54 ]. Overall, these severe life-threatening adverse events are occurring rarely, thus supporting the ongoing rollout of global vaccination programs.…”
Section: Discussionmentioning
confidence: 99%
“…A DVT has also been reported shortly after the second dose of an mRNA-based vaccine as well [ 52 ]. Anaphylaxis as an acute allergic reaction has also been reported as a rare event for some vaccines, such as mRNA COVID-19 vaccines [ 53 ] and adenovector vaccines against COVID-19 [ 54 ]. Overall, these severe life-threatening adverse events are occurring rarely, thus supporting the ongoing rollout of global vaccination programs.…”
Section: Discussionmentioning
confidence: 99%
“… 78 The compound is present in COVID-19 vaccines, because the introduction of a pegylated nanoparticle surrounding mRNA impairs its enzymatic degradation, increases its water-solubility and, thereby, the bioavailability of lipid nanoparticles. 75 , 79 Despite the fact that PEGs are considered to be compounds with the low potential of triggering allergic reactions, the most commonly described hypersensitivity reactions were IgE-dependent. Moreover, some authors reported cases of anaphylactic shock and complement activation-related pseudoallergy.…”
Section: Adverse Reactions To Hyaluronic Fillers and The Sars-cov-2 Epidemicmentioning
confidence: 99%
“…This syndrome has been associated with several diseases, a variety of drugs or environmental exposures [8]. Although vaccine ingredients may be considered potential inducers of allergic events [9], KS induced by vaccines is a very rare clinical condition. Only few cases of allergic myocardial infarction due to tetanus and influenza vaccines have been previously reported [10,11].…”
Section: Introductionmentioning
confidence: 99%